2016
DOI: 10.1080/0167482x.2016.1199544
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ perspectives on the acceptability and uptake of HPV vaccines in Zimbabwe

Abstract: This study provides insight from healthcare providers about barriers to implementation and possible solutions that can be used by policy makers, practitioners, and other stakeholders to facilitate the successful implementation of forthcoming HPV immunization programs in Zimbabwe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…[24]. Some male stakeholders expressed disinterest in HPV vaccination, assuming that since it is a female-directed vaccine aimed at addressing cervical cancer, that HPV must not affect men [15,23,36]. The focus on cervical cancer (and by extension, the necessity of having a cervix in order to be directly affected), coupled with a traditional cultural focus of reproductive health being a part of a "woman's job", reinforced feminization of HPV and caused feelings of resentment, confusion, and distrust towards HPV vaccination from some stakeholders of both sexes in SSA [15,28].…”
Section: Perception That Infertility Is a Results Of The Hpv Vaccinementioning
confidence: 99%
“…[24]. Some male stakeholders expressed disinterest in HPV vaccination, assuming that since it is a female-directed vaccine aimed at addressing cervical cancer, that HPV must not affect men [15,23,36]. The focus on cervical cancer (and by extension, the necessity of having a cervix in order to be directly affected), coupled with a traditional cultural focus of reproductive health being a part of a "woman's job", reinforced feminization of HPV and caused feelings of resentment, confusion, and distrust towards HPV vaccination from some stakeholders of both sexes in SSA [15,28].…”
Section: Perception That Infertility Is a Results Of The Hpv Vaccinementioning
confidence: 99%
“…In order to make this public policy decision, it is essential to consider acceptability of the vaccine among healthcare users, 29,34,35,38,39,48 logistical aspects of vaccine implementation 42,[52][53][54] as well as the need for providing current, accurate information to healthcare professionals about the safety and efficacy of HPV vaccination among adults in general and specifically those living with HIV. [55][56][57][58] Although our findings must be interpreted with care given the cross-sectional design, they indicate, as other studies have shown, that healthcare provider recommendation is an extremely important factor for encouraging HPV vaccination among people living with or without HIV. 45,53,55,56 This is especially important if healthcare providers are to support such public policies by recommending the HPV vaccine to their patients.…”
Section: Discussionmentioning
confidence: 74%
“…[55][56][57][58] Although our findings must be interpreted with care given the cross-sectional design, they indicate, as other studies have shown, that healthcare provider recommendation is an extremely important factor for encouraging HPV vaccination among people living with or without HIV. 45,53,55,56 This is especially important if healthcare providers are to support such public policies by recommending the HPV vaccine to their patients. 45,53,55,56 Knowledge about HPV was high; in our study, 84% of participants knew that HPV can cause cancer, which compares favorably to another study of women living with HIV where only 50% knew about this association.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations